Literacy Lessons and a Reading Contest to Improve Students’ Reading Comprehension (A Case of Students in an Indonesian Senior High School, SMAN 1 Soe) - Yabes Olbata; Marike Nelwan; Getreda Y Oematan (English Education Department - Universitas Nasional Karangturi, 2022)
Teaching and learning is a good way to reach the educational goals. This is a classroom action research. The objective of this study was finding out how reading literacy improve students’ comprehension. This study used mix method design. The instruments used were test. The data of this study were collected through spreading questionnaires and doing interviews. The result of the study showed reading literacy could improve students’ comprehension. The data analysis showed that there was a significant improvement of students’ comprehension in cycle I compared to cycle II. It was because reading literacy could facilitate students in identifying problems, brain storming, analyzing, formulating problems, and presenting well.